Peremptory norms as an aspect of constitutionalisation in the international legal system - Orakhelashvili, Alexander (Hague Academic Press, 2009)
The phenomenon of constitutionalisation occupies increasing place in the discourse on international law, even though the international legal system contains no formal and express constitutional arrangement. The two basic features of constitution are that it regulates the issues of basic importance for the relevant community, and it prevails over ordinary laws. The phenomenon of peremptory norms of international law (jus cogens) satisfies both these requirements. The ground covered by jus cogens relates to the area of interests of the international community as a whole, safeguarding which is the concern for all. It is also a natural function of jus cogens to prevail over ordinary norms of international law. Thus, whether or not jus cogens is part of constitution of the international society, it performs the functions of it, compatibly with its other principal function as public order (public policy) of the international society. The expressions of this constitutional element relate to the possibilities of invoking its primacy over ordinary laws in international and national courts, on matters such as the immunity of States or the powers of international organizations. The interaction between the powers of the UN Security Council and jus cogens demonstrates how the original public policy aspect of jus cogens - its non-derogability - could generate the classical constitutional supremacy over treaty-based institutional arrangements.
Keywords: Peremptory Norms (jus cogens); Theory of international law; Human rights; UN Security Council resolutions; State immunity; Prosecution of international crimes